The Effectiveness of Interpersonal Communication in Online Learning in Providing Communication Science Students at the University of Muhammadiyah Madiun - Fajar Istikhomah; Aprilia Tri Mawarni; Anggita Aulia Al Rasyid; Jerry; Mifta Khudin; Rhavida Anniza Andyani (Perspective Humanities and Social Sciences, 2025)
This research aims to find out whether interpersonal communication in online learning can help students of the Muhammadiyah University of Madiun communication science study program learn better. The approach taken in this research is a quantitative approach which focuses on testing theory by measuring or calculating research variables and using statistical techniques to analyze data. In this research all questions were made in Google form with a Likert scale. The sampling method used is the Slovin formula by entering confidence and error levels of 95% and 10% respectively. This research also uses the interpersonal communication characteristics of empathy, openness, positive feelings, equality, and support to evaluate how effective interpersonal communication is in providing students with an understanding of online learning. The results of this research are that the interpersonal communication process of online learning in providing understanding to Communication Science study program students at Muhammadiyah University of Madiun is quite effective. In the process of providing understanding, lecturers have an important role such as opening space for discussion and sharing opinions, providing additional information such as companion books for student learning needs, taking the time to provide guidance to students who are having difficulty and providing fair grades for the assignents they have completed student.